‘Qiu Zhijie’s self-conception as an artist – doing art in a critical historical and transcultural perspective’ - Birgit Hopfener (Journal of Art Historiography, 2014)
This essay examines Qiu Zhijie’s self-conception as an artist. The point of departure is the artist’s concern that ‘art must transform life’. Based on a selection of artworks and critical writings and focusing specifically on his concept of ‘Total Art’ (zongti yishu) the article introduces how Qiu Zhijie re-thinks the classical idea of art as self-cultivation as a critical historical and transcultural practice of connecting and interrelating with reality. It is in this context that the essay presents Qiu Zhijie’s practice of self-cultivation as the pursuit of social change on the one hand, and in relation to his role as a critical historiographer on the other hand.